2024
DOI: 10.1200/jco.23.01367
|View full text |Cite
|
Sign up to set email alerts
|

Survival Trends Among Adolescents and Young Adults Diagnosed With Cancer in the United States: Comparisons With Children and Older Adults

Theresa H.M. Keegan,
Renata Abrahão,
Elysia M. Alvarez

Abstract: PURPOSE Although data from 1975 to 1997 revealed a gap in cancer survival improvement in adolescents and young adults (AYAs; 15-39 years) compared with children and older adults, more recent studies have reported improvements in AYA cancer survival overall. The current analysis provides an update of 5-year relative survival and cancer survival trends among AYAs compared with children and older adults. METHODS We obtained data from the National Cancer Institute Surveillance, Epidemiology, and End Results Progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…The 5-year survival in our case series is slightly higher than that which is described in a recent epidemiological study on the U.S. population, which reports a 5-year relative survival in older adults (>40 years) of 77.5% and in adolescents and young adults (AYAs, 15-39 years) of 68.7%. The worse prognosis in AYAs may be explained by the higher incidence of HIV-associated KS among young patients [38].…”
Section: Discussionmentioning
confidence: 99%
“…The 5-year survival in our case series is slightly higher than that which is described in a recent epidemiological study on the U.S. population, which reports a 5-year relative survival in older adults (>40 years) of 77.5% and in adolescents and young adults (AYAs, 15-39 years) of 68.7%. The worse prognosis in AYAs may be explained by the higher incidence of HIV-associated KS among young patients [38].…”
Section: Discussionmentioning
confidence: 99%
“…AYAs exist at the margins of pediatric and adult cancer care, and neither system is adequately equipped to address the needs of this population [4]. As a result, AYAs experience significant unmet needs [5,6] and poorer psychosocial and medical outcomes compared to other age groups [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Often referred to as cancer's "forgotten generation" [9], AYAs experience health disparities across the cancer continuum. Survival rates for AYAs have not kept pace with improvements achieved for cancers in children and older adults [7] due in part to systemic factors such as delays in diagnosis, inadequate accrual of AYAs into clinical trials, and lack of funding and research for AYA cancers [3,10,11]. AYA cancer survivors, who, given their age, will live for several decades beyond their diagnosis, face disproportionately greater medical, psychosocial, and financial impacts compared to older adult survivors [12].…”
Section: Introductionmentioning
confidence: 99%
“…Osteosarcoma, an intensely aggressive malignant tumor originating from bone, predominantly affects adolescents (1)(2)(3). Recent studies have revealed that disruptions in metabolic pathways and alterations in the immune microenvironment significantly contribute to the pathogenesis of osteosarcoma (4-7).…”
Section: Introductionmentioning
confidence: 99%